ANALISIS TINGKAT KOGNITIF PADA ITEM TES MEMBACA BERDASARKAN KURIKULUM 2013 DAN KURIKULUM MERDEKA - Alpha Yerni Safitri; Rika Afriyanti; Melvina (Yayasan Pendidikan Literasi Borneo, 2025)
This study aims to analyze the cognitive levels of reading test items based on the 2013 Curriculum and the Merdeka Curriculum, with a particular focus on Higher Order Thinking Skills (HOTS). This research employed a qualitative descriptive method with document analysis as the main approach. The data were obtained from the final semester examination of grade XII students, consisting of 47 reading test items from the 2013 Curriculum (academic year 2022/2023) and 37 reading test items from the Merdeka Curriculum (academic year 2024/2025). The analysis was conducted using the Revised Bloom’s Taxonomy framework, which classifies cognitive levels into C1–C3 (Lower Order Thinking Skills/LOTS) and C4–C6 (HOTS: analyzing, evaluating, and creating). The findings reveal that the 2013 Curriculum contains 14 HOTS items (12 analyzing and 2 evaluating), while the Merdeka Curriculum contains 13 HOTS items (10 analyzing and 3 evaluating). These results indicate that both curricula integrate HOTS in reading assessments, although with different distributions. Despite their relatively limited proportion, the presence of HOTS items reflects the curricula’s attention to developing students’ critical, analytical, and evaluative thinking skills. Therefore, it is suggested that teachers enhance both the quality and quantity of HOTS-based questions to better prepare students for the demands of 21st-century learning.